Application of Special Needs Children Learning at RA Ar-Rafif Kalasan Yogyakarta - Munastiwi, Erni (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
Education is the right for all citizens without exception for children with disabilities. This research aims to describe the process of implementation of children with special needs in educational institutions Raudhatul Athfal/kindergarten. Research methodology using qualitative methods of field studies with observation techniques, interviews, and documentation. The results of thestudy gained that in the application of children with special needs (autistic and ADHD), learning in RA Ar-Rafif began from planning, implementation, and evaluation. Child-specific learning needs to implemented in regular classes. Learning for children with special needs is shadow and unaccompanied. Implementation of learning without any coercion, using children's center methods and learning safeguards for children with disabilities according to their interests. Evaluation and assessment of child-specific learning with anecdotal assessment, communication and parental information when the child is at home, daily activities and work. Evaluation is conducted one semester one to three times according to needs